Why Patients Miss Scheduled Outpatient Appointments at Urban Academic Residency Clinics: A Qualitative Evaluation - Ofei-Dodoo, Samuel; Kellerman, Rick; Hartpence, Connor; Mills, Kale; Manlove, Emily (Kansas Journal of Medicine, 2019)
Introduction Missed outpatient appointments are a common problem for academic residency clinics, and reducing their rate improves office efficiency, income, and resident education. Identifying specific reasons why some patients miss outpatient appointments may provide insight into developing targeted approaches to reducing their rates. This study sought to find reasons associated with patients’ missed appointments at two family medicine residency clinics. Methods The study utilized a qualitative research design involving patients at two urban, university-affiliated family medicine residency outpatient clinics. Twenty-five randomly selected patients who were dismissed from the clinics for missing three or more scheduled appointments during a five-year span (July 2012 to July 2017) were interviewed over the phone about reasons they did not keep their scheduled clinic appointments. The authors, individually and as a group, used an immersion-crystalization approach to analyze the content of the interviews. Results Responses from 25 participants (21 females and four males) are presented. Fifty-two percent of patients were Caucasian, 32% Black, 12% Hispanic, and 4% Asian. Five themes emerged from the data analysis as major reasons the patients missed their scheduled outpatient appointments: forgetfulness, transportation issues, personal health issues, family and employer obligations, and other issues, such as anticipated long clinic wait times, bad weather, and financial problems. Conclusions The findings showed there are several logistical, situational, and clinical reasons for patients’ missed scheduled outpatient appointments.